Effect of educational neuroscience techniques in the university aural skills classroom - Horton, Staci Marie (Kansas State University, 2018)
The purpose of this study was to test student achievement in the course of one semester while enrolled in an Aural Skills music classroom. The research used the framework from Caine and Caine’s 1991 Brain/Mind Learning Principles (later revised and republished in 2005 by Caine, Caine, McClintic and Klimek) and Jensen’s Brain-Compatible Teaching theory (1997). The research was completed at a mid-American university. Treatment classrooms taught using strategies to implement novelty, student engagement, and scaffolding success techniques based on a subset of Caine’s et al. Brain/Mind Learning Principles. The researcher used a quasi- experimental design with a treatment and control group, gathering quantitative pre-test/post-test data from student assessments before and after the implementation of the research-based brain- compatible strategies in the university Aural Skills classroom. The study followed four graduate teaching assistants who were new to collegiate teaching over the course of a semester; two were put in a training program and trained on how to create novelty, perpetuate student engagement, and build levels of success and two were left alone, to continue with a lecture style of teaching. At the end of the study, student test scores were examined to determine significance of the treatment. Results of this study are inconclusive, due to a methodology fail during the grading of the pre and post-tests. In the final chapter, preliminary findings indicate that academic gains were maintained within the control classes of Aural Skills I and III, and academic gains were maintained within the treatment class of Aural Skills II. The study is concluded with a discussion on methodological improvements necessary to provide reliable results within the bounds of educational research.
Keywords: Education; Brain-Based; Educational Neuroscience; Aural Skills; Music; Collegiate Teaching Strategies